Advanced Nanoengineering Approach for Target‐Specific, Spatiotemporal, and Ratiometric Delivery of Gemcitabine–Cisplatin Combination for Improved Therapeutic Outcome in Pancreatic Cancer. Issue 2 (10th November 2021) - Tarannum, Mubin; Hossain, Md Akram; Holmes, Bryce; Yan, Shan; Mukherjee, Pinku; Vivero‐Escoto, Juan L.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an intractable malignancy with a dismal survival rate. Recent combination therapies have had a major impact on the improvement of PDAC prognosis. Nevertheless, clinically used combination regimens such as FOLFIRINOX and gemcitabine (Gem)/nab‐paclitaxel still face major challenges due to lack of the safe and ratiometric delivery of multiple drugs. Here, a rationally designed mesoporous silica nanoparticle (MSN)‐based platform is reported for the target‐specific, spatiotemporal, ratiometric, and safe co‐delivery of Gem and cisplatin (cisPt). It is shown that systemic administration of the nanoparticles results in synergistic therapeutic outcome in a syngeneic and clinically relevant genetically engineered PDAC mouse model that has rarely been used for the therapeutic evaluation of nanomedicine. This synergism is associated with a strategic engineering approach, in which nanoparticles provide redox‐responsive controlled delivery and in situ differential release of Gem/cisPt drugs with the goal of overcoming resistance to Pt‐based drugs. The platform is also rendered with additional tumor‐specificity via a novel tumor‐associated mucin1 (tMUC1)‐specific antibody, TAB004. Overall, the platform suppresses tumor growth and eliminates the off‐target toxicities of a highly toxic chemotherapy combination. Abstract : A multifunctional mesoporous silica nanoparticle (MSN)‐based platform for the target‐specific, spatiotemporal, ratiometric, and safe co‐delivery of gemcitabine (Gem) and cisplatin (cisPt) is developed. This platform efficiently suppresses tumor growth and eliminates the off‐target toxicities of this highly toxic chemotherapy combination in a syngeneic and clinically relevant genetically engineered pancreatic ductal adenocarcinoma (PDAC) mouse model.